Pendampingan Penyusunan Eletronik Rencana Definitif Kebutuhan Kelompok (E-RDKK) Menggunakan Teknologi Google Form Pada Gabungan Kelompok Tani “Rejo Mulyo” Kabupaten Bondowoso - Rizal, Rizal; Rizal, Togimin (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The general aim of this service activity is to increase students' insight and understanding regarding the process of submitting and preparing subsidized fertilizer requirements through E-RDKK and train apprentices to get used to solving problems using the knowledge gained on campus. The implementation of PPPM socializes the usefulness and benefits of preparing the E-RDKK for farmers, Poktan administrators, and farming business planners. Socialization and training regarding the flow and procedures for preparing the E-RDKK received a positive response. With this training, farmers understand the flow of preparing the E-RDKK. Gapoktan Rejo Mulyo's response to internship activities in providing socialization and training in preparing the E-RDKK in accordance with the SOP has had a positive impact. Before carrying out PPPM activities, Gapoktan members assumed that preparing the E-RDKK was the responsibility of agricultural instructors. This is because while they were Gapoktan administrators, Poktan was not fully involved and did not know the flow of preparing the E-RDKK. With this activity, there was socialization and training on the preparation of the E-RDKK, and Gapoktan and Poktan administrators became aware of their responsibilities as Gapoktan and Poktan administrators. Based on interviews with Gapoktan and Poktan administrators, it is hoped that socialization, training, and mentoring activities will be more intensive.